The Effectiveness of Soulface Band's Music Presentation on the Attractiveness of Fameliza Cafe Visitors - Nisa Aprilia Mayang Sari (Universitas Negeri Surabaya, 2026)
Music plays an important role in life, especially in the entertainment industry. Live music performances in cafes provide direct entertainment, creating a relaxed atmosphere and attracting visitors. This study uses a mixed-methods design that combines qualitative and quantitative approaches. In the initial qualitative stage, the study explored the form of the Soulface band's music presentation through observation and interviews with band members. The quantitative stage involved distributing questionnaires to 66 cafe visitors to measure the effectiveness of the presentation in attracting visitors. The data were analyzed using simple linear regression to assess the relationship between presentation format and visitor attraction. The second qualitative stage then explored the impact of music presentation descriptively through interviews with three visitors. The study's results show that Soulface's performance is compelling and significant in attracting visitors. In addition, live music has a positive impact on visitors' cognitive, emotional, behavioral, social, and symbolic aspects. These findings confirm that music has a strategic role in supporting business success, especially in creating appeal and positive experiences in cafes.